Chlorogenic acid inhibits NLRP3 inflammasome activation through Nrf2 activation in diabetic nephropathy - Liping Bao; Yuhan Gong; Wenji Xu; Jun Dao; Jinjin Rao; Haihui Yang (PLoS ONE, 2025)
Diabetic nephropathy (DN) is the single largest cause of end-stage renal disease (ESRD). Inflammation reaction mediated by NLRP3 inflammasome and Nrf2-related oxidative stress have been considered to play a very important role in the progress of diabetic nephropathy (DN). Effective drugs for the treatment of diabetic nephropathy still need to be explored. Chlorogenic acid (CGA) is a kind of polyphenol with a Nrf2 activation property widely existed in nature. The aims of this study were to evaluate the renoprotective effect of CGA and to elucidate the anti-inflammation mechanisms involved. In the present study, we established a diabetic rat model to investigate the renoprotective effect of CGA in vivo. The results show that the level of serum creatinine (Scr), blood urea nitrogen (BUN), and urinary protein excretion in diabetic rats were significantly decreased after CGA intervention. CGA administration can active the Nrf2 pathway and inhibit NLRP3 inflammasome activation. Notably, Nrf2 siRNA transfection nullified the inhibitory effects of CGA on NLRP3 inflammasome activation in vitro. To summarize, our present study provided evidence that chlorogenic acid can slow the progression of diabetic nephropathy progression, and the effect is associated with suppression of NLRP3 inflammasome activation via through modulation of the Nrf2 pathway, suggesting its therapeutic implications for diabetic nephropathy.